Diagnostic Accuracy of Coronary Artery Calcium Scoring in Detecting Significant Coronary Artery Stenosis Compared with Invasive Coronary Angiography - Adelbertus Erico; Rusli Muljadi; Mira Yuniarti; Ingrid Maria Pardede; Andree Kurniawan; Patricia Jorizal (Medicinus, 2026)
Background: Coronary artery disease (CAD) remains a leading cause of mortality, emphasizing the importance of early non-invasive diagnostic strategies. This study evaluated the diagnostic accuracy of coronary artery calcium scoring (CACS) in detecting significant coronary stenosis, using invasive angiography as the reference standard.   Methods: Sixty-three patients who underwent both CACS and quantitative coronary angiography were retrospectively analyzed. The mean total CACS was 684.1 ± 1030.8, and significant stenosis (≥70%) was most prevalent in the left anterior descending artery (92.1%).   Result: Spearman’s analysis revealed positive correlations between CACS and angiographic stenosis in the right coronary artery (ρ = 0.338, p = 0.007), left anterior descending artery (ρ = 0.492, p = 0.001), and left circumflex artery (ρ = 0.314, p = 0.012). Receiver operating characteristic (ROC) analysis demonstrated moderate-to-good diagnostic performance, with area under the curve (AUC) values of 0.699 for RCA, 0.769 for LAD, and 0.690 for LCX.   Conclusions: These findings indicate that CACS can serve as a reliable, low-cost, and non-invasive modality for preliminary screening and risk stratification of CAD, particularly in identifying patients who may benefit from invasive coronary angiography.